2010
DOI: 10.1002/cphc.201000533
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric Aqueous‐Phase Free‐Radical Chemistry: Radical Sources, Spectra, Reaction Kinetics and Prediction Tools

Abstract: The most important radicals which need to be considered for the description of chemical conversion processes in tropospheric aqueous systems are the hydroxyl radical (OH), the nitrate radical (NO(3)) and sulphur-containing radicals such as the sulphate radical (SO(4)(-)). For each of the three radicals their generation and their properties are discussed first in the corresponding sections. The main focus herein is to summarize newly published aqueous-phase kinetic data on OH, NO(3) and SO(4)(-) radical reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
396
4
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(427 citation statements)
references
References 157 publications
(221 reference statements)
16
396
4
1
Order By: Relevance
“…Kinetic data for aqueous phase reactions with OH are available or can be estimated based on structurereactivity-relationships (e.g. Ervens et al, 2003b;Herrmann, 2003;Monod et al, 2005;Monod and Doussin, 2008;Minakata et al, 2009;Herrmann et al, 2010). Most OH reactions with organic compounds are near the diffusion limit in the aqueous phase (k = 10 9 -10 10 M −1 s −1 ).…”
Section: Carbonyl Compounds (≤C 5 )mentioning
confidence: 99%
“…Kinetic data for aqueous phase reactions with OH are available or can be estimated based on structurereactivity-relationships (e.g. Ervens et al, 2003b;Herrmann, 2003;Monod et al, 2005;Monod and Doussin, 2008;Minakata et al, 2009;Herrmann et al, 2010). Most OH reactions with organic compounds are near the diffusion limit in the aqueous phase (k = 10 9 -10 10 M −1 s −1 ).…”
Section: Carbonyl Compounds (≤C 5 )mentioning
confidence: 99%
“…This latter choice makes this SAR simpler to implement but it lowers its prediction performance. This may explain why, in their thorough comparison of the robustness of the two SARs for alkanes, mono-alcohols, poly-alcohols, and carboxylic acids, Herrmann et al (2010) found that the SAR proposed by Monod and Doussin (2008) performed better and was therefore eventually implemented as an extension of the CAPRAM 3.0i mechanism whenever possible (Herrmann, 2012).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…In these media, organic compounds are known to undergo oxidation by a number of radicals, among which OH radicals are the most reactive oxidants (Herrmann et al, 2010). This reactivity initiates chain reactions that are related to atmospherically important issues such as the oxidizing capacity of the atmosphere (Monod and Carlier, 1999;Monod et al, 2007;Poulain et al, 2010;Ervens et al, 2013), the fate of organic compounds (Blando and Turpin, 2000;Monod et al, 2005) and the formation of secondary organic aerosol (SOA) (Altieri et al, 2006;Carlton et al, 2007;Volkamer et al, 2009;Ervens and Volkamer, 2010;Tan et al, 2010Tan et al, , 2012Lim et al, 2010;Ervens et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, laser flash photolysis was used to study the kinetics of this process. Sulfate ion radicals were generated through the photolysis of peroxodisulfate ions initiated by a laser pulse at 266 nm: [53][54][55][56][57] …”
Section: Direct Study Of the Sulfate Ion Radical With Silver(i)mentioning
confidence: 99%